Study on Performance of Different Wound Dressings on Surgical Non Infected Wounds - S. Kubera Sampath Kumar; C. Prakash; S. Subramanian (Journal of Natural Fibers, 2021)
This study conducted to understand the limitations of existing wound-dressing systems. A case study on healing performance of different types of commercially available wound dressings was conducted at Madras Medical College and Government General Hospital (MMC&GH), Chennai, Tamil Nadu, India (Ethical Clearance No. 3250/ME5/2010). The study indicated that the single-layer dressing would not satisfy most of the requirements of an ideal wound-dressing system, and hence there is the need for developing a multilayer wound-dressing system with each layer satisfying different requirements of an ideal wound-dressing system.